SNO-EANO-EURACAN consensus on management of pineal parenchymal tumors - Liu, Anthony P.Y.; Li, Bryan K; Vasiljevic, Alexandre; Dewan, Michael C; Tamrazi, Benita; Ertl-Wagner, Birgit; Hansford, Jordan R; Pfaff, Elke; Mynarek, Martin; Ng, Ho-Keung; Tsang, Derek S; Gottardo, Nicholas G; et al. (Neuro-Oncology, 2024)
Pineal parenchymal tumors are rare neoplasms for which evidence-based treatment recommendations are lacking. These tumors vary in biology, clinical characteristics, and prognosis, requiring treatment that ranges from surgical resection alone to intensive multimodal antineoplastic therapy. Recently, international collaborative studies have shed light on the genomic landscape of these tumors, leading to refinement in molecular-based disease classification in the 5th edition of the World Health Organization (WHO) classification of tumors of the central nervous system. In this review, we summarize the literature on diagnostic and therapeutic approaches, and suggest pragmatic recommendations for the clinical management of patients presenting with intrinsic pineal region masses including parenchymal tumors (pineocytoma, pineal parenchymal tumor of intermediate differentiation, and pineoblastoma), pineal cyst, and papillary tumors of the pineal region.